New Developments in Medicine Through Artificial Intelligence and Advances in Biotechnology – An Overview - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2024)
Medicine has changed rarely in history as rapidly as it is today. Constantly new methods are being introduced that can improve health outcomes. Six such developments are presented here: 1. artificial intelligence (AI) in diagnosis and treatment; 2. 3D-printed organs; 3. tele-surgery; 4. nano-medicine; 5. CRISPR technology; 6. quantum teleportation. Thus several problems in medicine can be solved, to the benefit of patients. However, this also increases the responsibility of users to apply the methods in accordance with ethical principles.